Influence of nitrogen concentration on electrical, mechanical, and structural properties of tantalum nitride thin films prepared via DC magnetron sputtering - Dastan, Davoud; Shan, Ke; Jafari, Azadeh; Gity, Farzan; Yin, Xi-Tao; Shi, Zhicheng; Alharbi, Najlaa D.; Reshi, Bilal Ahmad; Fu, Wenbin; Ţălu, Ştefan; Aljerf, Loai; Garmestani, Hamid; et al. (Applied physics. A, Materials science & processing, 2022)
Tantalum nitride thin films are grown on silicon wafers using a mixture of Ar/N 2 using DC magnetron sputtering. The influence of nitrogen concentration on various features of tantalum nitride thin films is systematically studied. X-ray diffraction results show characteristic peaks of FCC tantalum nitride with crystallite size gradually increasing upon an augmentation in the nitrogen concentration. Field emission scanning electron microscopy images indicate that the tantalum nitride thin films are made of crystal domains with almost regular boundaries. As nitrogen concentration increases from 10 to 25%, the average domain size increases. Atomic force microscopy (AFM) results show larger surface roughness for the tantalum nitride thin films with higher nitrogen concentration owing to grain boundary diffusivity. Furthermore, quantitative characterization of 3-D surface morphology from AFM micrographs is obtained by multifractal and stereometric analyses. The results of mechanical properties show a decrease in the hardness upon increasing the nitrogen concentration due to variation in the grain size. The obtained results from the four-point probe illustrate that the specimen with higher nitrogen content displays the minimum sheet resistance due to a decrease in inter-grain boundaries emanated from the larger grain size. The current study renders a new insight in controlling the conductivity and the hardness of TaN thin film based on the deposition conditions and provide a correlation between the structural and other properties of TaN films, which is useful for a variety of semiconductor devices.